The Late Holocene tephra record of the central Mediterranean Sea: Mapping occurrences and new potential isochrons for the 4.4–2.0 ka time interval - D. D. Insinga; P. Petrosino; I. Alberico; G. J. de Lange; C. Lubritto; F. Molisso; M. Sacchi; R. Sulpizio; J. Wu; F. Lirer (Journal of Quaternary Science, 2020)
Five cores from the southern Tyrrhenian and Ionian seas were studied for their tephra and cryptotephra content in the 4.4–2.0 ka time interval. The chronological framework for each core was obtained by accelerator mass spectrometry 14 C dating, the occurrence of distinct marker tephra and stratigraphic correlation with adjacent records. Tephrochronology allowed us to correlate the analyzed deposits with tephra markers associated with Somma‐Vesuvius (79 ad ), Ischia Island (Cretaio), Mt Etna (FG, FL and FS) and Campi Flegrei (Astroni‐Agnano Monte Spina) events. For the first time in the marine setting, a large single glass data set is provided for the Late Holocene Etnean marker beds including the FS tephra (ca. 4.3 ka). Moreover, unknown deposits from Lipari (ca. 2.2–2.0 ka) and Vulcano (3.6–3.3 ka) are also recognized at more distal sites than previously reported. These results contribute to improve the high‐resolution tephrostratigraphic framework of the central Mediterranean Sea. They also provide new insights into the chemical composition and dispersal pattern of tephras that can be used as inter‐archive tools for regional and ‘local’ stratigraphic correlations and for addressing paleoclimate research.

Late Holocene sedimentary changes in shallow water settings: the case of the Sele river offshore in the Salerno Gulf (south-eastern Tyrrhenian Sea, Italy) - Francesca Budillon; Maria Rosaria Senatore; Donatella D. Insinga; Marina Iorio; Carmine Lubritto; Mariangela Roca; Paola Rumolo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Major and trace element characterization of tephra layers offshore Pantelleria Island: insights into the last 200 ka of volcanic activity and contribution to the Mediterranean tephrochronology - Stella Tamburrino; Donatella D. Insinga; Mario Sprovieri; Paola Petrosino; Massimo Tiepolo (Journal of Quaternary Science, 2012)
A detailed tephrochronological study was carried out on the deep‐sea core collected from Site 963A in the Sicily Channel during ODP Leg 160. The chronology of the succession is provided by an age–depth model based on isotope stratigraphy and quantitative eco‐biostratigraphy. Major, trace and rare earth element content was obtained on single glass grains through electron probe micro‐analysis and laser ablation–inductively coupled plasma mass spectrometry techniques from six well‐preserved tephra layers, characterized by a discrete thickness found along the succession. These deposits were correlated with the volcanic activity of Pantelleria and dated at 42.5, 127.5, 128.1, 129.1, 188.7 and 197.7 ka. This detailed chemical characterization of the studied deposits aims to provide a valuable reference database for scientists working on both proximal and distal products erupted at Pantelleria island during the Late Pleistocene. This study, moreover, offers the opportunity to better identify Pantelleria‐related marker tephras within the tephrochronological framework of the central and eastern Mediterranean area. Copyright © 2012 John Wiley & Sons, Ltd.

Reply to the comment on the article “40Ar/39Ar dating of tuff vents in the Campi Flegrei caldera (southern Italy): toward a new chronostratigraphic reconstruction of the Holocene volcanic activity” by Isaia et al. - L. Fedele; D. D. Insinga; A. T. Calvert; V. Morra; A. Perrotta; C. Scarpati (Bulletin of Volcanology, 2012)

40Ar/39Ar dating of tuff vents in the Campi Flegrei caldera (southern Italy): toward a new chronostratigraphic reconstruction of the Holocene volcanic activity - L. Fedele; D. D. Insinga; A. T. Calvert; V. Morra; A. Perrotta; C. Scarpati (Bulletin of Volcanology, 2011)